Contribution to the knowledge of Iranian Pygopleurus Motschulsky, with description of P. rapuzzii n. sp. (Coleoptera: Scarabaeoidea: Glaphyridae) - Keith, Denis; Uliana, Marco (Zootaxa, 2008)
A new species of Glaphyridae is described: Pygopleurus rapuzzii n. sp. from northwestern Iran. The new species is sympatric with and shares many character states with P. anahitae Mitter, from which it can be differentiated by the shape of genital parts and by morphological characters of head, pronotum, and elytra. Both species are illustrated for the first time. New records from Iran are given for other species of the genus Pygopleurus Motschulsky.